Psychological Adaptation of Islamic Education Teachers In Implementing the Merdeka Curriculum: A Phenomenological Study at Nurul Hijrah Sukamara - Selly Mayang Sari; Hamdanah Hamdanah; Surawan Surawan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The Merdeka Curriculum requires teachers to have psychological readiness in responding to more flexible and student-centered learning changes. However, studies that specifically examine the psychological experiences of Islamic Religious Education teachers remain limited. This study aims to explore the dynamics of PAI teachers’ psychological experiences in implementing the Merdeka Curriculum and to identify their adaptation patterns. This research used a qualitative approach with a phenomenological design involving three informants, consisting of one principal and two PAI teachers at SMP Nurul Hijrah Sukamara. Data were collected through in-depth interviews, observation, and documentation, then analyzed using thematic analysis through transcription, coding, categorization, and theme extraction. The findings reveal four stages of psychological adaptation: initial uncertainty, professional pressure, adaptive learning, and professional confidence. At first, teachers experienced anxiety and pressure due to project-based learning, differentiated instruction, and administrative demands. Over time, teachers showed increased competence and confidence through spiritual coping, time management, social support, and professional development. This study develops the Teacher Psychological Adaptation to Curriculum Reform model.